Blood Culture Isolates and Antibiogram of Salmonella: The Gathering Storm - Reza, Ishrat Binte; Ahasan, HAM Nazmul; Ahmed, Moshtaque; Tahseen, Homayra; Chowdhury, Tasmina (KYAMC Journal, 2020)
Introduction: Typhoid fever is a common problem all over the world including Bangladesh. It is caused by salmonella typhae and paratyphae and it is an old infectious water born disease. It is encountered in Bangladesh throughout the year. For many years it is treated by Chloramphenicol and subsequently Cotrimoxazole and Amoxicillin. Despite the use of newly developed antibacterial drugs, enteric fevers caused by multidrug-resistant bacterial strains are one of major health problems in Bangladesh. Multidrug resistant Salmonella sp. has been emerged is a cause of concern. Materials and Methods: This is a retrospective study done at the Popular Medical College Hospital over a period of 6 months between January 2018 to june 2018. Results: During the study period, total 115 cases were enrolled. Regarding antibiotic sensitivity pattern, 69% strains were sensitive to Ampicillin, 100% to Cefixime and Ceftriaxone, 75% to Cotrimoxazole, 52% to Nalidixic Acid and 68% to Ciprofloxacin, 69% to Levofloxacin, 80% to Cholarphenicol. Conclusion: Ceftriaxone and Cefixime were found to be highly sensitive. So, we should be very careful for the judicious use of these valuable drug to prevent drug resistance. KYAMC Journal Vol. 10, No.-4, January 2020, Page 188-190